The Prevention of Rh-Immunization - Bowman, John M. (1977)
Administration of Rh immune globulin to the Rh-negative unimmunized woman at risk of Rh-immunization is highly effective if given in sufficient dose prior to active Rh-immunization. Remaining problems are: 1. treating all of those at risk, 2. protecting those who abort, 3. treating after amniocentesis, 4. instituting an antenatal prophylaxis program to protect the 1.8 percent immunized too early to be protected by post-delivery injection of Rh immune globulin, 5. protecting those who have had massive transplacental fetal hemorrhages. All physicians practicing obstetrics should ensure that all of their unimmunized Rh-negative women are protected against Rh-immunization.